COVID-19 Context in PISA-Like Mathematics Problems - Yurika Mariani; Ratu Ilma Indra Putri; Hapizah Hapizah; Milhana Betty (Universitas Sriwijaya, 2022)
This development research aims to produce PISA-like mathematics problems with quantity content using a valid and practical COVID-19 context and to investigate the potential effect of these problems on mathematical literacy skills. This research employed a development research design with two stages: preliminary and formative evaluations. This study also employed the Lesson Study Learning Community (LSLC) system in the process of development and implementation. This study involved eighth-grade students aged 13-15 years at SMP Negeri 19 Palembang. The data were collected using walk-through, document, observation, interview, and test techniques. This study produced 6 units and 12 items of PISA-like mathematics problems with several content characteristics of the COVID-19 context, including working, personal, and social contexts and levels that agree with the 2018 PISA framework; and competence processes, such as mathematical literacy skills and standardized linguistic skills that can be applied and interpreted by students. To conclude, the developed PISA-like mathematics problems are valid and practical and potentially affect mathematical literacy skills and learning to confront life skills during the COVID-19 pandemic.